STRATEGI DINAS PERHUBUNGAN KABUPATEN OGAN KOMERING ULU DALAM TATA KELOLA LALU LINTAS DI KECAMATAN BATURAJA TIMUR - Dedy Hartono; Aprilia Lestari; Eva Susanti; Yahnu Wiguno Sanyoto (Jurnal Riset Multidisiplin Edukasi, 2026)
The increase in the number of motor vehicles that is not proportional to road capacity has caused traffic problems in Baturaja Timur District, Ogan Komering Ulu Regency. Traffic congestion mainly occurs during peak hours due to commercial, educational, and office activities. This study aims to analyze the strategy of the Ogan Komering Ulu Regency Transportation Agency in traffic governance based on good governance principles. The research employed a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The results indicate that traffic governance strategies have been implemented through traffic management and engineering, field supervision, and the provision of supporting facilities. However, their implementation still faces constraints related to resource limitations, community participation, and policy sustainability.